Green Strategy–Based Synthesis of Silver Nanoparticles for Antibacterial Applications - Ssekatawa, Kenneth; Byarugaba, Denis K.; Kato, Charles D.; Wampande, Eddie M.; Ejobi, Francis; Nakavuma, Jesca L.; Maaza, Malik; Sackey, Juliet; Nxumalo, Edward; Kirabira, John B. (Frontiers in Nanotechnology, 2021)
Antibiotics have been the nucleus of chemotherapy since their discovery and introduction into the healthcare system in the 1940s. They are routinely used to treat bacterial infections and to prevent infections in patients with compromised immune systems and enhancing growth in livestock. However, resistance to last-resort antibiotics used in the treatment of multidrug-resistant infections has been reported worldwide. Therefore, this study aimed to evaluate green synthesized nanomaterials such as silver nanoparticles (AgNPs) as alternatives to antibiotics. UV-vis spectroscopy surface plasmon resonance peaks for AgNPs were obtained between 417 and 475 nm. An X-ray diffraction analysis generated four peaks for both Prunus africana extract (PAE) and Camellia sinensis extract (CSE) biosynthesized AgNPs positioned at 2θ angles of 38.2°, 44.4°, 64.5°, and 77.4° corresponding to crystal planes (111), (200), (220), and (311), respectively. A dynamic light-scattering analysis registered the mean zeta potential of +6.3mV and +0.9 mV for PAE and CSE biosynthesized nanoparticles, respectively. Fourier transform infrared spectroscopy spectra exhibited bands corresponding to different organic functional groups confirming the capping of AgNPs by PAE and CSE phytochemicals. Field emission scanning electron microscopy imaging showed that AgNPs were spherical with average size distribution ranging from 10 to 19 nm. Biosynthesized AgNPs exhibited maximum growth inhibitory zones of 21mm with minimum inhibitory concentration and minimum bactericidal concentration of 125 and 250 μg/ml, respectively, against carbapenem-resistant bacteria
Keywords: green synthesis; silver nanoparticles; antibiotic resistance